“Reflecting Forward” on the Digital in Multidirectional Memory-Work Between Canada and South Africa - Strong-Wilson, Teresa; Mitchell, Claudia; Morrison, Connie; Radford, Linda; Pithouse-Morgan, Kathleen (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2014)
We explore the place that the digital can occupy in teachers’ pedagogical practices around social justice and especially how memory-work can deepen and enhance teacher practices. Like Walter Benjamin, we see memory as being a medium for exploring the past and where the digital provides greater opportunities for teachers to work productively across geographical contexts that are wrestling with issues of social justice. We argue for the potential of Michael Rothberg’s notion of multidirectional memory as a logical direction in which to pursue notions of cross-border, transnational productive remembering facilitated by digital means. We also pose a number of questions we see as critical for working through and “reflecting forward” on issues central to digital scholarship within the context of multidirectional memory.